2017
DOI: 10.1093/pm/pnw316
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-Derived ADAM10 Production Stimulates Peripheral Nerve Injury–Induced Neuropathic Pain by Cleavage of E-Cadherin in Satellite Glial Cells

Abstract: Our findings indicate that neuron-derived ADAM10 production stimulates peripheral nerve injury-induced neuropathic pain by cleaving E-cadherin in satellite glial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Furthermore, Wnt/ β-catenin signaling was also reported to be negatively regulated by PS1 [ 35 ]. ADAM10 was suggested to cleave E-cadherin, which is mainly expressed in satellite glial cells [ 36 ]. Our data from the FpClass PPI prediction tool indicate that ADAM10 might interact with E-cadherin and ADAM17 rather than the other secretases or APP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Wnt/ β-catenin signaling was also reported to be negatively regulated by PS1 [ 35 ]. ADAM10 was suggested to cleave E-cadherin, which is mainly expressed in satellite glial cells [ 36 ]. Our data from the FpClass PPI prediction tool indicate that ADAM10 might interact with E-cadherin and ADAM17 rather than the other secretases or APP.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of this systematic review, inflammation decreases when NM is applied 10 days after CCI, as shown by the reduction of most inflammatory molecules. GFAP is a marker of activated satellite glial cells in PNS, which increases after CCI and nerve ligation in rodents (50,51). Substance P, IL-1β and TRPV1 also contribute to inflammatory responses related to rodent neuropathic pain (52)(53)(54)(55).…”
Section: Authormentioning
confidence: 99%